Spatial Autocorrelation in the Analysis of the Land Property Market on the Example of Szczecin and Bydgoszcz - Batóg, Barbara; Foryś, Iwona; Gaca, Radosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The location of the real estate is the most important determinant of its value. Location does not change, therefore the value of real estate strongly depends on factors specific to a given area within a city. Topography influencing a possibility of land development, territorial development, installations and road infrastructure as well as the neighbourhood have great influence over the price of the real estate. All these factors are connected with buyers’ preferences and with transactional price, unit price and value of the property. The aim of the paper is to analyse the influence of the relative position of the examined real estates on their prices; and comparison of results obtained for Szczecin and Bydgoszcz. In order to achieve this aim Moran’s I Statistic and spatial autoregressive model were applied. The data came from notarial deeds from registers of real estate prices and values concerning transactions on land ownerships on unbuilt land properties in 2014 in Szczecin and Bydgoszcz.